Place- and community-based education in schools - Smith, Gregory A.; Sobel, David (b, 2010)
Explains the purpose and nature of place- and community-based education and provides multiple examples of its practice. This book contains descriptions of learning experiences set both within and beyond the classroom which will help readers begin the process of advocating for or incorporating local content and experiences into their schools.
Includes bibliographical references and index.
Keywords: z; Community and school -- United States; Education -- General. -- Teaching Methods & Materials